Math, asked by parichoudhary07, 8 months ago

1 - 2ab - (a2 + b2) = ?
(a) (1 + a - b)(1 + a + b)
(c) (1 + a + hl( - a - b)
(b) (1 + a + b)(1-a+b)
(d) (1 + a - b)(l - a + b)​

Answers

Answered by sanujsethiya
0

Answer:

2ab×(2a+2b)

=2ab+4a^2b+4ab^2

2ab+8a^3b^3

Answered by infotmondal16
3

Answer:

(d) (1 + a - b)( 1 - a + b)

Step-by-step explanation:

1 - 2ab - (a² + b²)

= 1 - (a² + 2ab + b²)

= (1)² - (a - b)²

= (1 + a - b)( 1 - a + b)

Hope it will help you thanks.

please give a thanks and mark as brainliest.

Similar questions